2001
DOI: 10.1136/adc.85.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Long term complications of inferior vena cava thrombosis

Abstract: Aim-To evaluate the long term outcome after paediatric inferior vena cava (IVC) thrombosis. Methods-A combined retrospective and prospective study on infants and children with IVC thrombosis treated at Aachen and Maastricht University Hospitals between 1980 and 1999. Results-Forty patients were enrolled, including four with preceding cardiac catheterisation, 18 with central venous saphenous lines, and an additional eight with umbilical venous catheters. Six patients died within three months of diagnosis; one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 27 publications
1
72
0
5
Order By: Relevance
“…A flow chart of search results and their distribution by category of publication is provided in Figure 1, showing both included [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and excluded reports. Nineteen original reports met eligibility criteria (Table 1); no systematic reviews were identified.…”
Section: Overall Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A flow chart of search results and their distribution by category of publication is provided in Figure 1, showing both included [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and excluded reports. Nineteen original reports met eligibility criteria (Table 1); no systematic reviews were identified.…”
Section: Overall Search Resultsmentioning
confidence: 99%
“…74 Components of each of these outcome measures are summarized in Figure 2. The remaining 11 studies [3][4][5][6][7]9,12,15,17,19,21 did not indicate the use of a standardized outcome measure.…”
Section: Overall Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleeding risk reported in this cohort was low. PTS is a particular concern for long-term morbidity in children who can be expected to live for many decades after a thrombosis (Manco-Johnson et al, 2000;Hausler et al, 2001).…”
Section: Morbidity and Mortality Associated With Vte In Childrenmentioning
confidence: 99%
“…Neonatal hypercoagulability resulting in thrombosis of the IVC has been described in association with hereditary thrombophilia and antiphospholipid antibodies. Indeed, Hausler et al reported 5/22 patients with IVC thrombosis having protein S deficiency or factor V Leiden mutation 20 .…”
Section: Discussionmentioning
confidence: 99%